The role of internal marketing in achieving customer satisfaction An exploratory study of a sample of private bank managers in Baghdad - Mahdi, Ahmed Ghazi; Jathir, Saadoun Hammoud (Journal of Economics and Administrative Sciences, 2020)
This study examined the effect of elements of internal marketing activities on customer satisfaction through an exploratory study of banking services in the city of Baghdad, if the research problem crystallized by asking a group of questions, the most important (is there a correlation and impact between the dimensions of internal marketing and customer satisfaction, this study aims to determine The effect of internal communication, training and internal market research on customer satisfaction, represented by the quality of service, loyalty and market share, and embodied the objective of this study to identify the level of availability of internal marketing activities and programs in the research banks, data were collected using a questionnaire-based survey consisting of (24) questions and distributed 102)) as director of the managers of private banks in the city of Baghdad. In order to analyze the data obtained from the questionnaires, using quantitative methods such as the arithmetic mean, the standard deviation, the difference coefficient, the simple correlation coefficient, and the modelling of the structured equation, the researcher reached a number of conclusions, the most important of which is the existence of relationships Correlation and influence of moral significance between internal marketing and its dimensions, customer satisfaction and its dimensions, and this confirms that the research banks are interested in the activities of this marketing. Leave three (internal communication, training, internal market research) that will lead to the result in achieving customer satisfaction. Accordingly, the research recommended that the research banks should instruct the administration to improve the internal marketing activities by applying the activities appropriate to the bank’s work to obtain customer satisfaction, and the search was limited to private banks, so it is not possible to generalize the results to the rest of the service organizations, and that providing internal marketing activities and programs in the researched banks contribute In reaching the customer’s satisfaction, the research shares support the social responsibility of the banks searching for customers, considering that individuals are part of this society and that any impact on it affects the society as a whole.